Intensive versus standard blood pressure control and vascular procedures: insights from the Systolic Blood Pressure Intervention Trial. (25th November 2020) - Byrne, C; Pareek, M; Rujic, D; Krogager, M.L; Kragholm, K.H; Biering-Soerensen, T; Vaduganathan, M; Olesen, T.B; Olsen, M.H; Bhatt, D.L
Abstract: Background: The Systolic Blood Pressure Intervention Trial (SPRINT) found that intensive versus standard blood pressure control reduced cardiovascular (CV) morbidity and mortality. Previous studies have shown that control of blood pressure reduces the risk of stroke and is one of the most modifiable risk factors for carotid artery disease. On the other hand, data on effect of blood pressure control on peripheral artery disease are more diverse. In addition, it is unknown whether intensive blood pressure control affects the risk of vascular procedures. Purpose: To assess the relationship between intensive blood pressure control and incident vascular procedures. Methods: SPRINT was a randomized, controlled trial comprising 9, 361 individuals ≥50 years of age at high CV risk but without diabetes who had a systolic BP (SBP) 130–180 mmHg. Patients were randomized to intensive (target SBP <120mmHg) or standard antihypertensive treatment (target SBP <140mmHg). The primary efficacy endpoint was the composite of acute coronary syndromes, stroke, heart failure, or death from CV causes. The primary safety endpoint was the composite of serious adverse events. We examined the risk of composite and individual vascular procedures with intensive versus standard blood pressure control. We further examined subgroup heterogeneity using interaction analyses. Results: During a median follow-up time of 3.3 years (range 0–5.5 years), a total of 174 (1.9%) composite vascular procedures were recorded. Intensive blood pressure control did not significantly reduce the risk of composite vascular procedures (intensive blood pressure control, 76 (1.6%) versus standard blood pressure control, 98 (2.1%), hazard ratio 0.76, 95% confidence interval, 0.57 to 1.03; P=0.08) (Figure 1). Similarly, the risks of the individual endpoints of carotid angioplasty, carotid endarterectomy, peripheral angioplasty or thrombolysis, lower extremity amputation for ischemia and gangrene, surgical or vascular procedure for abdominal aortic aneurysm, surgical or vascular procedure for thoracic aortic aneurysm, and surgical or vascular procedure for other problems were not significantly affected (P≥0.05 for all). Intensive blood pressure control reduced the risk of peripheral vascular surgery (intensive blood pressure control, 7 (0.2%) versus standard blood pressure control, 21 (0.5%), hazard ratio 0.33, 95% confidence interval, 0.14 to 0.77; P=0.01), though this was based on a small number of events. The safety and efficacy of intensive BP lowering was not modified by chronic kidney disease, age, sex, race, previous cardiovascular disease, or baseline systolic blood pressure tertile (P≥0.05 for all). Conclusions: In SPRINT, intensive versus standard blood pressure control did not reduce the risk of composite incident vascular procedures. Funding Acknowledgement: Type of funding source: None